Pengaruh Cognitive Behavior Therapy Dalam Menurunkan Anxiety Sebagai Upaya Optimalisasi Fungsi Mental Pasien Kanker Serviks - june, junaidi (Universitas Islam Negeri Raden Intan Lampung, 2019)
Until now, cervical cancer is still a cause of female mortality which is quite high, estimated at 4,900 people per year. When doctors diagnose a person suffering from a dangerous (chronic) disease such as cancer, there are three forms of emotional responses that may generally appear, namely rejection, anxiety and depression. Anxiety that often occurs in cervical cancer patients is a negative emotion that causes individuals to feel afraid, worried and concerned about something, the source is realistic or not, and ultimately motivates the individual to take concrete action in response to the existing anxiety.This study was conducted to examine the effect of CBT therapy in reducing anxiety levels of cervical cancer patients, using quantitative and qualitative research methods. The combination of quantitative and qualitative methods will help researchers to better understand the phenomenon being studied. The quantitative method in this study uses descriptive analysis.Based on the results obtained from this study, it was seen that there was a decrease in the degree of anxiety in cervical cancer patients who were the subject of this study after being intervened by using cognitive behavior therapy (CBT).An effective change occurs in cervical cancer sufferers after being given CBT therapy where positive effects are felt such as feeling calmer, more energetic and optimistic to recover in the face of the disease. Giving CBT therapy makes the process of cognitive assessment of patients to change. Social support that comes from families such as husband and children and the surrounding environment can provide strength and motivation to recover for patients with cervical cancer